EVALUATION OF PSYCHIATRIC MORBIDITY IN ADOLESCENTS IN PATIALA DISTRICT, PUNJAB - Sidhu, Tanvir Kaur (Indian Journal of Community Health, 2012)
Background:What is the morbidity pattern of the adolescent patients coming to seek treatment in Psychiatry Deptt.? Objectives: To evaluate the pattern of mental disorders in adolescents. Methods:The study was a hospital based cross-sectional study conducted in the Deptt. of Psychiatry, Rajindra Hospital,Patiala. 500 adolescents aged 10-19 were interviewed. Results: More of the morbid patients were from nuclear families, 6.4% were married among whom, 2.4% were either divorced or separated.13.2% patients had positive history of any family member having psychiatric problem. Only 21.2% had contacted a psychiatrist at first instance while 50.8% had been to traditional healers. The most common diagnosis was Mood (affective) disorders followed by neurotic, stress-related and somatoform disorders. Next was mental retardation followed by schizophrenia and delusional disorders .The most common diagnosis among males was neurotic, stress related and among females was mood disorders. The difference of distribution of diagnosis among urban and rural , nuclear and joint families was statistically significant. Conclusion: Patients reporting to the hospital with psychiatric disorders were urban males. Most of the patients were eldest in birth order and belonged to nuclear families. Most of the patients had been to traditional healers. The most common diagnosis was mood disorders followed by neurotic stress related illness.